(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
We have employed UV light absorption and circular dichroism methods to study the binding of water-soluble Co(II)-containing meso-tetra-(4N-oxyethylpyridyl) porphyrin (CoTOEPyP4) with B- and A-DNA from Calf Thymus. The binding constant Kb we determined from binding isotherms for each DNA–porphyrin complexes and calculated binding free energy ΔG, enthalpy ΔH and entropy ΔS. Our results suggest that CoTOEPyP4 porphyrin preferably binds via outside self-stacking mode with B- and A-DNA.